Age-Related Changes in the Neural Processes of Reward-Directed Action and Inhibition of Action - Le, Thang M.; Chao, Herta; Levy, Ifat; Li, Chiang-Shan R. (Frontiers in Psychology, 2020)
Aging is associated with structural and functional brain changes which may impact the regulation of motivated behaviors, including both action and inhibition of action. As behavioral regulation is often exercised in response to reward, it remains unclear how aging may influence reward-directed action and inhibition of action differently. Here, we addressed this issue with the fMRI data of 72 participants (aged 21-74) performing a reward go/no-go (GNG) task with approximately 2/3 go and 1/3 no-go trials. Go and no-go success trials were rewarded with a dollar or a nickel, and incorrect responses were penalized. An additional block of the GNG task without reward/punishment served as the control to account for age-related slowing in processing speed. The results showed prolonged response time in rewarded (vs. control) go trials with increasing age. Whole-brain multiple regressions of rewarded (vs. control) go trials against age and RT both revealed age-related reduced activity of the anterior insula, middle frontal gyrus, and rostral anterior cingulate cortex. Further, activity from these regions mediated the relationship between age and go performance. During rewarded (vs. control) no-go trials, age was associated with increased accuracy rate but decreased activation in the medial superior frontal and postcentral gyri. As these regions also exhibited age-related activity reduction during rewarded go, the finding suggests aging effects on common brain substrates that regulate both action and action inhibition. Taken together, age shows a broad negative modulation on neural activations but differential effects on performance during rewarded action and inhibition of action.